Investigation of postural balance control in judo and handball players - Ahmet Sanıoglu; Cengiz Taskın; Mine Taskın; Onder Karakoc (Selcuk University, 2015)
The aim of this study was to examine postural balance control in hudo and handball players. A total of 50 healthy athletes that are judo and handball players participated as volunteer. The mean (SD) age was 20.96 ± 1.18 years, height was 1.66 ± 0.07 mm, and weight was 60.26 ± 0.07 kg for the 23 female athletes; the mean (SD) age was 21.82 ± 1.77 years, height was 1.77 ± 0.07 m, and weight was 83.66 ± 19.65 kg for the 27 male athletes. Postural balance control was evaluated using the single-legged Flamingo balance test. No significant differences were observed for female and male (P gt;0.05). On the other hand, we found significant differences for judo and handball players as generally (P lt;0.05). Also, we found significant differences between judo and handball for male athletes (P lt;0.05) and judo and handball for female athletes (P lt;0.05). However, we found significant differences between male judoka and female judoka (P lt;0.05). On the other hand, there are no significant differences between male handball players and female handball players (P gt;0.05). In conclusion, it was found that postural balance control of judoka is better than handball players' postural balance control. Also, it was less postural balance control of female judoka than postural balance control of female handball players. In male athletes, this was the exact opposite.